WHY WE BLOG? THE MALAYSIAN TRAVEL BLOGGER AND TOURIST PERSPECTIVE - N Alia Fahada W Ab Rahman (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Travel blogs as research data have been widely used in the tourism context. Acknowledging the growth of travel blogs and blogs application in tourism, there is a need to understand the blogging motivation, which in also could shed some light of blogosphere behaviour. This study therefore, aims to investigate the travel bloggers behaviour and motivation that influence their engagement with travel blogs. Through in-depth interviews with 19 Malaysian travel bloggers this study shows that tourists bloggers had four main motivation that influence their motivation for creating and keeping travel blogs. This study accesses the demographic of travel blogs creators, blogging behaviour and the motivation for creating and keeping travel blogs. This study uncovers four main motivations namely altruistic, personal, hedonic and social motivation. Superficially, this study highlights that travel blogs are more than just a means of gathering information and sharing the tourist experience. Travel bloggers engage with travel blogs for entertainment and to communicate with the readers, to express their self-identity and also for social networking. Implications for future research is suggested.